PERSEPSI PELAKU USAHA MENENGAH KECIL DAN MIKRO TERHADAP ASURANSI SYARIAH - Mahanara Puja Kusuma (Diponegoro Journal of Islamic Economics and Business, 2025)
MSME Actors have an important role in economic development and growth. This research aims to analyze the perceptions of small entrepreneurs regarding sharia insurance among MSMEs in Argomulyo District, Salatiga. This type of research is descriptive with a quantitative approach. Data collection was carried out through a questionnaire with a Likert scale. The research was conducted in Argomulyo District with a sample of 30 MSMEs in Noborejo Village, Argomulyo Salatiga District, sampling was carried out using a purposive sampling technique. The research results concluded that MSME Actors have a positive perception of sharia insurance.